Sovereign risk and corporate cost of borrowing: Evidence from a counterfactual study - Marcin Wolski (European Investment Bank (EIB), 2018)
We assess the impact of the sovereign risk spill-overs onto corporate cost of borrowing in selected euro area countries. We utilize a novel nonparametric dependence filtering frame- work to remove the effects of sovereign risk in the interest rate pass-through context. The main findings confirm the heterogeneity in sovereign risk spill-overs. We also find divergence in sovereign risk transmission between core and peripheral Member States during financial and sovereign debt crises. We discover that the standard linear models may underestimate the underlying pass-through distortions, suggesting the existence of nonlinear sovereign risk effects.
Keywords: C14; E43; E52; G21; 330; counterfactual distributions; nonparametric methods; sovereign risk; cost of borrowing; pass-through